Analysis of the shoes in a population over 60 - López López, Daniel; Álvarez-calderón Iglesias, Óscar; Alonso Tajes, Francisco; Gómez Martín, Beatriz; Sánchez Gómez, Rubén (Revista Internacional de Ciencias Podológicas, 2008)
Footwear represents an essential part of garment of people in occidental culture. If utilized in a correct way, it provides protection and aid in human gait. Nevertheless, if utilized incorrectly, it’s related to falls, alterations in gait and appearance or worsening in foot pathology. In the present issue, we studied what style of footwear is the most commonly used in a community older of 60, if it was appropriate or inappropriate and if geriatric community had information enough to know what is the most appropriate